2020
DOI: 10.2105/ajph.2020.305755
|View full text |Cite
|
Sign up to set email alerts
|

Service Learning in Health Care for Underserved Communities: University of Iowa Mobile Clinic, 2019

Abstract: The University of Iowa Mobile Clinic (UIMC) is an interdisciplinary student-run free medical clinic founded in 2002. UIMC provides free health screenings, education, and basic services to underserved populations in Iowa: immigrants, refugees, migrant farmworkers, individuals experiencing homelessness, low-income individuals, and people who live in rural communities. Forty-four percent of patients surveyed use UIMC as their only source of care. Ninety-seven percent of patients surveyed rate care as excellent or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 5 publications
0
46
0
Order By: Relevance
“…While many services were part of ongoing initiatives, such as clinics and regular mobile outreach programs, 6 , 29 , 35 , 51 , 52 , 71 , 72 , 74 , 75 some were episodic as with annual influenza vaccinations and health fairs. 54 , 56 , 57 , 64 , 76 , 77 Delivery of healthcare services ranged from primary care, which is generally first point of contact in relation to a health concern, 19 , 20 , 53 , 78 to ongoing follow-up of chronic conditions like diabetes and cardiovascular disease 35 , 48 , 79 , 80 and specialty services, such as prenatal care, musculoskeletal clinic, psychiatry, gynecologic care, and surgery. 20 , 28 , 58 , 61 , 81 A few individual health care student-run initiatives provided a range of primary care, specialty services, and diagnostics that sometimes also provided a consistent, comprehensive, and ongoing source of care for clients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While many services were part of ongoing initiatives, such as clinics and regular mobile outreach programs, 6 , 29 , 35 , 51 , 52 , 71 , 72 , 74 , 75 some were episodic as with annual influenza vaccinations and health fairs. 54 , 56 , 57 , 64 , 76 , 77 Delivery of healthcare services ranged from primary care, which is generally first point of contact in relation to a health concern, 19 , 20 , 53 , 78 to ongoing follow-up of chronic conditions like diabetes and cardiovascular disease 35 , 48 , 79 , 80 and specialty services, such as prenatal care, musculoskeletal clinic, psychiatry, gynecologic care, and surgery. 20 , 28 , 58 , 61 , 81 A few individual health care student-run initiatives provided a range of primary care, specialty services, and diagnostics that sometimes also provided a consistent, comprehensive, and ongoing source of care for clients.…”
Section: Resultsmentioning
confidence: 99%
“…These health initiatives spanned a range of populations and health conditions, most commonly in the provision of care to persons who were uninsured, underserved, and/or considered to be at-risk. 6 , 18 , 29 , 35 , 45 , 51 , 61 , 64 , 68 , 71 , 72 , 76 , 85 , 88 , 91 Persons uninsured for healthcare services was 1 prominent population for student-run services, particularly through SRFCs, in much of the literature originating in the United States. 20 , 22 , 41 , 42 , 45 , 72 , 78 , 83 , 91 - 93 Uninsured status was closely associated with low socioeconomic standing, including poverty and the “working poor,” or not meeting criteria for Medicaid as in the case for many immigrants and refugees.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality of chronic disease management in SRFCs has been assessed, with evidence suggesting comparable care to other care settings. 5,[7][8][9][10][11][12][13][14][15] However, the efficacy of SFRCs at meeting national averages in women's cancer screenings has shown mixed results. One study found greater rates of mammography among their patients compared to national averages.…”
Section: Introductionmentioning
confidence: 99%
“…For many of these patients, SRFCs may be their only source of care. 5,6 As of 2014, SRFCs collectively provided over 37,000 annual patient visits. Quality of chronic disease management in SRFCs has been assessed, with evidence suggesting comparable care to other care settings.…”
Section: Introductionmentioning
confidence: 99%